Travelers’ intentions and behaviors regarding central bank digital currency use - Han, Heesup; Quan, Wei; Chua, Bee-Lia; Lho, Linda Heejung (Scientific Journal Publishers, 2024)
The use of central bank digital currency (CBDC) is an emerging issue in the tourism industry. We uncovered travelers’ intention with respect to CBDC adoption by broadening and intensifying the technology acceptance model (TAM). A total of 598 valid samples were examined and showed that TAM variables, confidence, competence, and consumer innovativeness sufficiently contribute to explicating the intention generation process of travelers for CBDC adoption. The cross-national influence of China and the US on the intention to adopt CBDC was also explored by adding nationality as a moderator. This research is one of few studies unearthing travelers’ behaviors for CBDC use, which enriches the extant tourism literature.